Reconciliation of National Laws and Foreign Agreements: Legal Certainty for MSMEs in Export-Import - Kusuma, Galih Satria Alit Widi; Darmawan, Didit; Hardyansah, Rommy (Journal of Social Science Studies, 2024)
International trade, particularly in the context of exports and imports, is one of the main pillars of global economic development. In Indonesia, micro, small and medium enterprises (MSMEs) play an important role in the domestic economy, but often face complex legal challenges. This study aims to analyses the reconciliation mechanism between national law and foreign agreements in international contracts for MSME exports and imports. Using qualitative literature study methods, this study identifies regulations that are still in force, including the Constitution of the Republic of Indonesia, the Civil Code, and laws related to trade and arbitration. The results of the study show that the existing legal framework provides legal certainty and protection for MSMEs, as well as creating an environment conducive to cross-border transactions. This study also highlights the importance of harmonization between national and international laws to prevent disputes and increase the competitiveness of MSMEs in the global market. These findings are expected to provide recommendations for the development of better policies to support MSMEs in international trade.